Phage Therapy, a Salvage Treatment for Multidrug-Resistant Bacteria Causing Infective Endocarditis - Helal F. Hetta; Zainab I. Rashed; Yasmin N. Ramadan; Israa M. S. Al-Kadmy; Soheir M. Kassem; Hesham S. Ata; Wedad M. Nageeb (Biomedicines, 2023)
Infective endocarditis (IE) is defined as an infection of the endocardium, or inner surface of the heart, most frequently affecting the heart valves or implanted cardiac devices. Despite its rarity, it has a high rate of morbidity and mortality. IE generally occurs when bacteria, fungi, or other germs from another part of the body, such as the mouth, spread through the bloodstream and attach to damaged areas in the heart. The epidemiology of IE has changed as a consequence of aging and the usage of implantable cardiac devices and heart valves. The right therapeutic routes must be assessed to lower complication and fatality rates, so this requires early clinical suspicion and a fast diagnosis. It is urgently necessary to create new and efficient medicines to combat multidrug-resistant bacterial (MDR) infections because of the increasing threat of antibiotic resistance on a worldwide scale. MDR bacteria that cause IE can be treated using phages rather than antibiotics to combat MDR bacterial strains. This review will illustrate how phage therapy began and how it is considered a powerful potential candidate for the treatment of MDR bacteria that cause IE. Furthermore, it gives a brief about all reported clinical trials that demonstrated the promising effect of phage therapy in combating resistant bacterial strains that cause IE and how it will become a hope in future medicine.